Bibliometric analysis of artisanal textile clothing - Durán-Méndez, Jorge Antonio; Almeraya-Quintero, Silvia Xochilt; Guajardo-Hernández, Lenin G.; Sangerman-Jarquín, Dora Ma.; Pérez-Hernández, Luz María (Revista Mexicana de Ciencias Agrícolas, 2026)
Studies on artisanal textile clothing (ATC) contribute to preserving this productive activity; this study aimed to conduct a bibliometric analysis on the topic of ATC using the Scopus digital library through the construction of an algorithm that allowed selecting documents that have addressed the subject during the last two decades and thus measure the scientific activity and identify the different study approaches from which it has been analyzed; the methodology used was divided into seven stages through which the consulted information was systematized; the metadata imported in CSV format were interpreted using the bibliometrix library of the RStudio program, version 4.4.2; among the main results, it was obtained that the scientific production on ATC in Scopus has increased by 4.7 times in the period analyzed, mostly under historical, anthropological and archaeological orientations, among others and with greater productivity within the Asian continent; likewise, greater connectivity was observed through the set of metadata via the term ‘traditional’ located in the abstract section; however, it is believed that within this segment of scientific production, it is necessary to develop research that addresses the current contexts on the ATC production, such as the value chain approach.